Endoscopic Feature of Upper Gastrointestinal Bleeding Patient in Soedarso General Hospital Pontianak - Yustar Mulyadi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2010)
Background: Gastrointestinal tract hemorrhage is an emergency condition most commonly caused by rupture of the esophageal varices with a mortality rate between 25-30% of cases. Gastrointestinal endoscopy is an accurate diagnostic used modality to identify lesions and locate bleeding in the upper gastrointestinal tract. The aims of this study were to determine the endoscopic features of upper gastrointestinal bleeding patients and distribution based on age and sex. Method: Retrospective study of endoscopic Results of upper gastrointestinal bleeding patients in Soedarso hospital, Pontianak, between January - June 2008. Results: There were 114 patients consisting of 75 (65.79%) male and 39 (34.21%) female. The findings from endoscopic examination were 46 (40.35%) cases of gastric ulcers, 23 (20.17%) cases of esophageal varices, 20 (17.54%) cases of errosive gastritis, 17 (14.91%) cases of duodenal ulcer, and 4 (3.5%) cases of esophageal mass/gastric mass. Conclusion: In this study the most common cause of upper gastrointestinal bleeding is gastric ulcer and it occurs more often in males compared to females.   Keywords: endoscopic feature, upper gastrointestinal, gastric bleeding